Implementasi Metode Cooperative Script Untuk Meningkatkan Keterampilan Siswa - Fika Ayu Sukma; Laili Etika Rahmawati (Paedagogie, 2022)
This study aims to find out how to improve reading skills and how to improve students' reading skills using the cooperative script method at SDN 3 Krobokan semester 1 of the 2021/2022 academic year. This research method uses classroom action research (CAR) in which this research is carried out in stages and multicycles in order to obtain valid data. The steps for implementing CAR are research planning, research implementation, observation of results, and reflection. This research was conducted in the fourth grade of SD Negeri 3 Krobokan, Juwangi District, Boyolali Regency, Central Java. The subjects in this study were fourth grade students of SD Negeri 3 Krobokan, in the odd semester of the 2021/2022 academic year with a total of 14 students, of which 6 of the 14 students were male, and 8 other students were female. The results of this study are to improve the reading skills of fourth graders, it is necessary to apply a cooperative script learning model. Because this model requires students to play an active role in the group learning process. This learning model requires students to pair up and also exchange information from the texts they have read, so that their reading skills can unconsciously develop. Judging from the results of the cycle test the implementation of the cooperative script model experienced a significant increase, namely, the average value before the implementation of the cooperative script model was 46.42. After the researchers conducted research in cycle 1, the average value of the fourth graders rose to 77.85. After the first cycle research was successful, the researcher continued the second cycle research, namely, to cycle 2 students' reading skills also increased, namely, the average value became 86.42.